Adopting Distributive and Compensatory Justice to Determine Optimal Tax Treatment for Corporate Donations - Younis A. Battal Saleh (Journal of Indonesian Constitutional Law, 2026)
This study aims to demonstrate how to determine the tax treatment of corporate donations in a scientifically correct manner that ensures the following: First, tax justice among donor companies. Second, justice and equality of rights among stakeholders. Third, avoiding the distortion of the thought of CSR. This study adopts the concepts of distributive and compensatory justice to determine optimal tax treatments for corporate donations. Evaluating corporate donations on the ground is essential to determine tax treatment under this approach. Based on the results of the evaluation, the following actions are taken: First, forming logical perceptions that reflect the explicit and implicit meanings of donations as they are in reality. Second, determining the type of justice (distributive or compensatory) that should be adopted as the basis for tax treatment. Using a distributive and compensatory justice approach that is based primarily on rational evaluation, this research article identified "seven possible scenarios" for the tax treatment of corporate donations. The central idea of using distributive and compensatory justice as a philosophical foundation for differentiating tax treatments is a significant and original contribution. It moves the debate beyond the simplistic "incentive or no incentive" question to a more nuanced inquiry: "what kind of tax treatment, for what kind of company, under what circumstances?". The proposed seven scenarios and the structured evaluation framework provide a powerful and justifiable foundation for policymakers to design more equitable and sophisticated tax systems. This approach could genuinely inform global tax reforms. Adopting a distributive and compensatory justice approach to determining optimal tax treatments for corporate donations can help protect the concept of CSR from distortion.